Evaluation of the Practice Program in SMK Abdi Negara Binjai - Muhammad Isa; Sartika Hutasuhut; Deni Kurniawan; Azhar Azhar; Sri Rezeqi Rafiqah Wardah Manurung (STAI Miftahul Ula Nganjuk, 2022)
This research was carried out at SMK Abdi Negara Binjai regarding the Evaluation of the Prakerin Program at the school, this study used a mixed method method, and the researchers aimed to understand the input stages (antecedents) carried out in the implementation of the internship program at SMK Abdi Negara Binjai, to determine the stages of the process. (transactions) are implemented in the implementation of the internship program at SMK Abdi Negara Binjai and to understand the stages of results (outputs) the program is implemented. As for this research, it is useful to provide benefits both theoretically and practically, such as providing an overview in carrying out the evaluation of the prakerin implementation by using the stake's countenance evaluation model so as to find out the extent of the shortcomings of this practice and how the ability to improve these deficiencies. the benefits above are theoretical benefits while practical benefits for schools this research can be used as evaluation material to improve the implementation of prakerin that has been carried out so that in the future schools can carry out activities well. One of the findings in this study reveals things that support the implementation of PRACTICE for students at SMK Abdi Negara Binjai. The things that support or support the implementation of the PRAKERIN program are the existence of program guidelines that are easy to understand and whose achievements can be measured, practical facilities that must be adequate both at school and at practice sites, mentoring resources, mental and physical readiness of PRAKERIN participants, and financial assistance from the committee. and the government is urgently needed for the achievement of goals and the successful implementation of learning and training in schools and including the implementation of the Industrial Work Practice program at SMK Abdi Negara Binjai